Pengaruh Fungsi Manajerial Kepala Ruangan terhadap Kualitas Pelayanan Keperawatan - Sidabutar, Novryanti; Nasution, Siti Saidah; Nasution, Siti Khadijah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the influence of the managerial function of the head of the room on the quality of nursing services at the Prof. Mental Hospital. DR. Muhammad Idrem Medan in 2023. The research method used is a quantitative research method with an analytical survey research design type. The data collection technique is by interview using a questionnaire. Data analysis techniques use univariate and bivariate analysis with simple linear regression statistical tests. The results obtained show that there is an influence on the implementation of the managerial functions of the head of the room including planning, organizing, directing, and supervising, including in the good category score range. In conclusion, there is an influence of the managerial function of the head of the room on the quality of nursing services at the Prof. Mental Hospital. DR. Muhammad Idrem Medan in 2023. Keywords: Head of Room, Managerial Function, Service Quality.